Labour supply and income tax changes: A simulation study for Finland - Mika Kuismanen (Bank of Finland, 2000)
It is well known that estimation of the labour supply function is complicated by the non-linearity of the individual s budget constraint.Non-linearity may be caused by a number of factors such as the structure of the tax/benefit scheme or overtime rates. Non-linearities also cause problems in interpreting the policy implications of the estimates.In this study we use a well-structured econometric labour supply model that mimics actual budget constraints as closely as possible to analyse the labour-supply effects of different income tax regimes and systems. In addition to the empirically-specified labour supply model, we construct, for the first time in Finland, a behavioural microsimulation model.Our intent is to contribute to the tax debate in Finland by simulating several suggested changes in the tax system.Our simulation results show that none of the proposed reforms are self-financing.Revenue-neutral move to a proportional tax system does not have major effects on labour supply.The most pronounced behavioural effects are achieved when marginal tax rates are reduced at the lower end of the income tax schedule.
URN:NBN:fi:bof-20140807412
Keywords: 330; microsimulation; labour supply; taxation